Study on the Erosion Characteristics of Non-spherical Particles in Liquid-solid Two-phase Flow - H. Z. Jin; Z. Y. Liao; J. F. Zhou; X. F. Liu; H. C. Yao; C. Wang (Journal of Applied Fluid Mechanics, 2023)
Elbow erosion, defined as wall thinning due to the continuous interactions between solid particles and surface, is a common phenomenon in catalyst addition/withdrawal pipeline systems used in residual oil hydrogenation units. This form of erosion can seriously affect the reliable pipeline operation. The present paper describes the construction of realistic cylindrical catalyst particles using the multi-sphere clump method and computational fluid dynamics/discrete element model simulations to study the erosion of pipe walls under different inlet velocities and particle aspect ratios. An optical shooting experiment is carried out to ensure the accuracy of the calculation method, and the model performance is compared using several existing drag models. The results show that the drag model of Haider & Levenspiel is more accurate than the others in revealing the actual cylindrical particle flow. A higher inlet velocity is observed to increase the kinetic energy of the particles and affect their spatial distribution. Specifically, when the Stokes number is greater than 113.7, the position of the maximum erosion rate shifts from the elbow’s outer wall to the inner wall. Cumulative contact energy is introduced to quantify two different types of particle-wall contacts. With a growing particle aspect ratio, the proportion of tangential energy gradually increases, which indicates that sliding is the main contact mode. The results presented in this paper provide a reference for engineering erosion calculations.